Social Networks in Limbo. The Experiences of Older Adults During COVID-19 in Ghana - Asante, Emmanuel Akwasi; Awuviry-Newton, Kofi; Abekah-Carter, Kwamina (Frontiers in Public Health, 2021)
While studies exploring COVID-19 and its global influence have begun, social networks and support among older adults in low and middle-income countries such as Ghana have been inadequate, despite its enormous relevance. Thus, the study presents the voices of senior citizens in Jamestown and their social networks during the COVID-19 pandemic in Ghana. Using a phenomenological qualitative approach, data were collected from 15 older adults through in-depth interviews on older adults’ social network experiences during COVID-19 pandemic situation. Participants generally struggled to maintain connections with their family members, friends, neighbours, and the community, especially during the lockdown. They ascribed their limited interaction to COVID-19 preventive measures, such as social distancing, limiting face-to-face, staying-at-home, and reducing physical contact with family and friends imposed by the government. Loneliness, stress, and depression are also linked to the breakdown of social networks. The findings provide a deeper understanding of the COVID-19 impact on older adults’ quality of life. This study recommends that older adults’ wellbeing and social connectedness be improved by considering interventions based on a wellbeing concept.